MONITORING PERANGKAT SISTEM JARINGAN MENGGUNAKAN RASPBERRY PI 3 PADA SATUAN KERJA PERENCANAAN DAN PENGENDALIAN DINAS PEKERJAAN UMUM PROVINSI JAMBI: MONITORING, RASPBERRY, DEVICE. - Sany, Ezrifal (FORTECH (Journal of Information Technology), 2019)
Maintenance of Information Technology devices, especially network devices, is needed to support daily work. To monitor network monitoring devices, it takes a long time if a problem occurs, because to find a problem, it is necessary to check one by one to check one device until the point of the problem is found. Of course this of course can hinder the work that uses these network devices, the use of desktop computers (PC) and cameras that have been used as supporting devices in monitoring network devices. However, the use of such hardware has resulted in electricity costs being quite expensive, the use of the Raspberry Pi 3 Mini PC is the right choice in dealing with the above problems. Because the use is simpler and does not need to incur large costs. So that it can be an alternative in the use of monitoring on a fairly large computer network.